2020
DOI: 10.1111/den.13828
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low dose rectal diclofenac for preventing post‐endoscopic retrograde cholangiopancreatography pancreatitis: Propensity score‐matched analysis

Abstract: Background: Acute pancreatitis is a major adverse event of endoscopic retrograde cholangiopancreatography (ERCP). Rectal administration of non-steroidal anti-inflammatory drugs (NSAIDs) decreases the incidence of post-ERCP pancreatitis (PEP). However, the efficacy of low dose rectal NSAIDs for preventing PEP remains controversial. Methods:We performed a retrospective study of 301 patients with native papilla and a body weight of <50 kg who underwent ERCP between September 2010 and October 2019. After July 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Rectal administration of low‐dose NSAIDs before ERCP did not show any preventive effect. This finding was consistent with previous studies 19,20 . On the other hand, administration of NSAIDs after ERCP was significantly high risk in the multivariable analysis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Rectal administration of low‐dose NSAIDs before ERCP did not show any preventive effect. This finding was consistent with previous studies 19,20 . On the other hand, administration of NSAIDs after ERCP was significantly high risk in the multivariable analysis.…”
Section: Discussionsupporting
confidence: 93%
“…This finding was consistent with previous studies. 19,20 On the other hand, administration of NSAIDs after ERCP was significantly high risk in the multivariable analysis. This suggests that post-ERCP NSAIDs reflect various factors related to operator's choice such as the actual difficulty of the procedures and the patient conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, a pancreatic duct (PD) stent is placed in case of unintentional PD cannulation. A Japanese propensity-score matched analysis shows that low dose diclofenac (25 mg) in patients with a body weight <50 kg is not effective [25]. A large international prospective observational study has shown no protective effect of chronic statin and aspirin use [26].…”
Section: Early Managementmentioning
confidence: 99%
“…1 Various studies focusing on preventing the occurrence of PEP have reported aggressive intravenous hydration with lactated Ringer's solution, rectal nonsteroidal antiinflammatory drugs (NSAIDs), and pancreatic duct (PD) stenting to be effective. 2,3 Deploying a covered self-expandable metal stent (CSEMS) is preferred for biliary drainage treatment for malignant biliary obstruction (MBO) because of its replaceability and longer patency period. 4,5 Prolonged lifetime of patients with unresectable pancreatobiliary cancers and the development of neoadjuvant therapy for resectable cancers underlie this trend.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic retrograde cholangiopancreatography (ERCP) is a crucial method for diagnosing and treating pancreatobiliary diseases; however, post‐ERCP pancreatitis (PEP) is estimated to occur in 4.5% of cases 1 . Various studies focusing on preventing the occurrence of PEP have reported aggressive intravenous hydration with lactated Ringer's solution, rectal nonsteroidal anti‐inflammatory drugs (NSAIDs), and pancreatic duct (PD) stenting to be effective 2,3 . Deploying a covered self‐expandable metal stent (CSEMS) is preferred for biliary drainage treatment for malignant biliary obstruction (MBO) because of its replaceability and longer patency period 4,5 .…”
Section: Introductionmentioning
confidence: 99%